2012
DOI: 10.1371/journal.pone.0038486
|View full text |Cite|
|
Sign up to set email alerts
|

REST Controls Self-Renewal and Tumorigenic Competence of Human Glioblastoma Cells

Abstract: The Repressor Element 1 Silencing Transcription factor (REST/NRSF) is a master repressor of neuronal programs in non-neuronal lineages shown to function as a central regulator of developmental programs and stem cell physiology. Aberrant REST function has been associated with a number of pathological conditions. In cancer biology, REST has been shown to play a tumor suppressor activity in epithelial cancers but an oncogenic role in brain childhood malignancies such as neuroblastoma and medulloblastoma. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 42 publications
3
102
0
2
Order By: Relevance
“…For example, in human medulloblastoma tumors (13) and normal human brain tissue (26), NRSF/REST staining was observed to be localized to the nuclei. Conti et al (14) also reported that in gliomas, NRSF/REST exhibited a nuclear staining pattern (14). In the present study, positive NRSF/REST staining was detected in the nuclei and cytoplasm in normal liver tissue; whereas, in liver carcinoma, NRSF/REST was predominantly detected in the cytoplasm.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…For example, in human medulloblastoma tumors (13) and normal human brain tissue (26), NRSF/REST staining was observed to be localized to the nuclei. Conti et al (14) also reported that in gliomas, NRSF/REST exhibited a nuclear staining pattern (14). In the present study, positive NRSF/REST staining was detected in the nuclei and cytoplasm in normal liver tissue; whereas, in liver carcinoma, NRSF/REST was predominantly detected in the cytoplasm.…”
Section: Discussionsupporting
confidence: 61%
“…Similar results have been previously observed in other tissues. For example, Conti et al (14) also reported that in normal human tissue, NRSF/REST immunoreactivity was detected in the cytoplasm of selected neurons. Furthermore, Orta-Salazar et al (27) reported that in the hippocampus of a 3xTg-AD mouse (a mouse model of Alzheimer's disease), the nuclei and cytoplasm were NRSF/REST-positive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations